Effects of age and zinc supplementation on transport properties in the jejunum of piglets. Issue 3 (21st July 2014) - Gefeller, E. M.; Martens, H.; Aschenbach, J. R.; Klingspor, S.; Twardziok, S.; Wrede, P.; Pieper, R.; Lodemann, U.
Summary: Zinc is effective in the prevention and treatment of post‐weaning diarrhoea and in promoting piglet growth. Its effects on the absorption of nutrients and the secretory capacity of the intestinal epithelium are controversial. We investigated the effects of age, dietary pharmacological zinc supplementation and acute zinc exposure in vitro on small‐intestinal transport properties of weaned piglets. We further examined whether the effect of zinc on secretory responses depended on the pathway by which chloride secretion is activated. A total of 96 piglets were weaned at 26 days of age and allocated to diets containing three different levels of zinc oxide (50, 150 and 2500 ppm). At the age of 32, 39, 46 and 53 days, piglets were killed, and isolated epithelia from the mid‐jejunum were used for intestinal transport studies in conventional Ussing chambers, with 23  μ m ZnSO4 being added to the serosal side for testing acute effects. Absorptive transport was stimulated by mucosal addition ofd ‐glucose orl ‐glutamine. Secretion was activated by serosal addition of prostaglandin E2, carbachol or by mucosal application of Escherichia coli heat‐stable enterotoxin (Stp ). Jejunal transport properties showed significant age‐dependent alterations (p < 0.03). Both absorptive and secretory responses were highest in the youngest piglets (32 d). The dietary zinc supplementation had no significant influence on jejunal absorptive and secretory responses. However, the pre‐treatment of epithelia with ZnSO4 in vitro led to a small but significant decrease in both absorptive and secretory capacities (p < 0.05), with an exception for carbachol (p = 0.07). The results showed that, in piglets, chronic supplementation with zinc did not sustainably influence the jejunal transport properties in the post‐weaning phase. Because transport properties are influenced by the addition of zinc in vitro, we suggest that possible epithelial effects of zinc depend on the acute presence of this ion.